2008
DOI: 10.1051/parasite/2008153333
|View full text |Cite
|
Sign up to set email alerts
|

Platyhelminth systematics and the emergence of new characters

Abstract: Summary :Since the inclusion of molecular data in modern phylogenetic analyses, significant progress in resolving the origins and radiation of flatworms has been made, although some key problems remain. Here I review developments in the supply and use of systematic characters that provide the basis for diagnosis and phylogeny reconstruction, that in turn have driven systematic revisions and the interpretation of broader evolutionary patterns and processes; focus is placed on the parasitic taxa. Although useful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…The presence of the long undulating membrane and continuous row of cortical microtubules in the aspidogastreans seem to be more related to the polyopisthocotylean monogeneans, which may support the assumption that the Monogenea are a paraphyletic group, formed by unrelated monopisthocotyleans and polyopisthocotyleans (Littlewood 2008).…”
Section: Discussionsupporting
confidence: 66%
“…The presence of the long undulating membrane and continuous row of cortical microtubules in the aspidogastreans seem to be more related to the polyopisthocotylean monogeneans, which may support the assumption that the Monogenea are a paraphyletic group, formed by unrelated monopisthocotyleans and polyopisthocotyleans (Littlewood 2008).…”
Section: Discussionsupporting
confidence: 66%
“…Among the Neoophora some Proseriata and some Fecampiidae have an arrangement of the ovary in the form of isolated follicles and collecting ducts. Recent molecular phylogenetic studies have shown that Adiaphanida (including Prolecitophora, Tricladida and Fecampiidae) are a sister taxon to the Neodermata, but Proseriata appear to be basal to Neodermata and Adiaphanida (Lockyer et al 2003, Willems et al 2006, Littlewood 2008.…”
Section: Phylogenetic Remarksmentioning
confidence: 99%
“…Furthermore, molecular analyses have considerably shifted our views on flatworm phylogeny (Lockyer et al, 2003a;Olson and Tkach, 2005;Littlewood, 2008;Perkins et al, 2010;Laumer and Giribet, 2014) with implications for older hypotheses of parasiteehost coevolution. Due to the patchy fossil record, establishing the phylogeny of flatworms is particularly important for establishing a timeline for the group.…”
Section: Introductionmentioning
confidence: 98%